LITERASI KEBENCANAAN SEBAGAI UPAYA MITIGASI DALAM MENGURANGI RESIKO BENCANA: SEBUAH TINJAUAN LITERATUR - Alqulby, Rafi Qurrota; Rusnaldi, Affuan; Nugraheni, Irma Lusi (Jurnal Samudra Geografi, 2025)
Indonesia is a meeting area of three major tectonic plates, namely the Indo-Australian plate, the Eurasian plate, and the Pacific plate which makes Indonesia often approached by natural disasters such as earthquakes, volcanic eruptions, and tsunamis. Disasters that occur will certainly cause vulnerability for the community to occur both material and life losses. A mitigation effort is needed to be able to minimize the impact of losses from disasters that occur. One concrete form that can be done is disaster literacy. The purpose of this study is to determine the relationship of disaster literacy as part of disaster mitigation in dealing with disaster risk. This research uses the Systematic Literature Review (SLR) method and searches using Google Scholar. The results of the research based on 6 articles that have been reviewed obtained that in reducing disaster risk, disaster literacy is proven as one of the mitigation efforts. With successful disaster mitigation efforts, it will minimize the possibility of losses caused by disasters that occur and ultimately form a disaster resilient community